Preparation method of composite copper foil coating with high surface compactness and smoothness
By using the synergistic effect of polyethylene glycol, MMTD and SPS in the composite copper foil coating, combined with a modified hyperbranched polyimide coating, the thermal deformation problem of the composite copper foil coating was solved, improving the cycle life and safety performance of the battery.
Patent Information
- Application Number
- CN202511521342.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-23
- Publication Date
- 2026-01-09
AI Technical Summary
Existing composite copper foil coatings suffer from thermal deformation due to thermal shrinkage in batteries, affecting the battery's cycle life and safety performance. Furthermore, existing technologies struggle to effectively improve the density and smoothness of the coating.
After magnetron sputtering a copper layer onto a polypropylene thin film, polyethylene glycol is added to the electroplating solution as an inhibitor, MMTD as a leveling agent, and SPS as a brightener. By controlling the deposition of copper ions, a dense and smooth composite copper foil coating is formed. Before electroplating, plasma treatment and a modified hyperbranched polyimide coating are applied.
The tensile strength and density of the composite copper foil were improved, enhancing the stability and safety performance of the battery, and extending the battery's lifespan and energy density.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite copper foil technology, specifically a method for preparing a composite copper foil coating with high surface density and smoothness. Background Technology
[0002] Battery cycle life, energy density, and safety performance are crucial considerations for the rapid development of new energy and electronic technologies. The current collector is an important component of a battery; it gathers the current generated by the battery's active materials, forming a larger current output. The performance of the current collector directly affects the battery's cycle life, energy density, and safety performance.
[0003] Currently, most lithium-ion and sodium-ion batteries on the market use copper or aluminum foil as current collectors. These current collectors are heavy and expensive, which is not conducive to controlling battery cost and improving energy density. Composite foil materials have a significant advantage over traditional foil materials in this regard. Composite foil current collectors typically have a "sandwich" structure, with a polymer layer on the inner layer and metal conductive layers on both sides. The metal layer on the surface of the composite current collector is thinner, while the polymer layer is lighter, which reduces the overall weight of the current collector and thus increases the energy density of the lithium-ion battery. Compared to traditional foil current collectors, the thinner metal layer on the surface of the composite current collector is more likely to break when the battery experiences thermal runaway, isolating the active material from the current collector and thus preventing the thermal runaway of the lithium-ion battery from continuing.
[0004] Although composite foil materials are low in cost and lightweight, the heat generated during battery cycling causes the composite current collector to thermally shrink. Excessive thermal shrinkage can lead to severe thermal deformation of the composite current collector, affecting battery life. In existing technologies, most composite copper foils use electroplating processes to thicken the copper layer, and conventional copper plating additives are used in the plating solution. This limits the tensile strength of the composite current collector, as well as the density and smoothness of the copper plating layer. Consequently, the energy density and cycle life of the battery cannot be effectively improved, leading to safety issues.
[0005] Therefore, the present invention provides a method for preparing a composite copper foil coating with high surface density and smoothness to solve the problems mentioned in the background art. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing a composite copper foil coating with high surface density and smoothness, so as to solve the problems mentioned in the prior art.
[0007] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a composite copper foil coating with high surface density and smoothness, comprising the following steps: Step 1: Take a polypropylene film and magnetron sputter a copper target onto its surface to form a sputtered copper layer, thus obtaining a polypropylene film containing a sputtered copper layer. Step 2: Place the polypropylene film containing the sputtered copper layer in the electroplating solution and electroplat it to form a composite copper foil coating with high surface density and smoothness.
[0008] Furthermore, in step 1, the thickness of the polypropylene film is 4 μm; In step 1, the thickness of the sputtered copper layer is 40nm~60nm.
[0009] Furthermore, in step 2, the thickness of the composite copper foil coating is 0.5μm~1μm.
[0010] Furthermore, in step 2, the electroplating process conditions are: temperature 25℃~35℃, current density 5mA / cm². 2 ~15mA / cm 2 Electroplating time: 5 min to 15 min.
[0011] Furthermore, in step 2, the electroplating solution includes the following components: copper sulfate, hydrochloric acid, brightener, leveling agent, polyethylene glycol, MMTD (2-mercapto-5-methyl-1,3,4-thiadiazole), and SPS (sodium polydithiopropane sulfonate).
[0012] Furthermore, the amount of copper sulfate added to the electroplating solution is 90 g / L to 100 g / L; The amount of hydrochloric acid added is 55ppm / L~60ppm / L; The addition amount of brightener and leveling agent is 2.0~2.5g / L; The addition amounts of polyethylene glycol, MMTD, and SPS are 0.5 mg / L to 1.0 mg / L.
[0013] Furthermore, the copper sulfate is added in the form of a solution, with a concentration of 70 g / L to 130 g / L; The hydrochloric acid is added in the form of a solution with a concentration of 100 g / L to 140 g / L.
[0014] Furthermore, the brightener is Jeremy Brightener 310A; the leveling agent is Jeremy Leveling Agent 200B.
[0015] Furthermore, the polyethylene glycol is obtained by the following process: Ethylene oxide, initiator, and catalyst are mixed and heated under a nitrogen atmosphere. After cooling, a neutralizing agent is added to adjust the pH to 6.5-7.0. The mixture is then filtered, distilled under reduced pressure, and purified to obtain polyethylene glycol.
[0016] Furthermore, the mass ratio of ethylene oxide, initiator and catalyst is (200~230):1:(0.006~0.012).
[0017] Furthermore, the process conditions for the heating reaction are as follows: reaction temperature 120℃~180℃, reaction time 8h~12h, reaction pressure 0.3MPa~0.8MPa, and ethylene oxide feed rate 5kg / h~15kg / h.
[0018] Furthermore, the initiator is one or both of water and ethylene glycol; The catalyst is potassium hydroxide; The neutralizing agent is one or both of phosphoric acid and glacial acetic acid.
[0019] Furthermore, the average molecular weight of the obtained polyethylene glycol is 10,000.
[0020] Furthermore, the preparation process of the MMTD is as follows: S1: Mix ethanol, methylhydrazine and potassium hydroxide, add carbon disulfide dropwise at 0℃~5℃, stir the reaction to obtain a reaction solution containing potassium dithiocarbamate containing methylhydrazine. S2: Mix the reaction solution containing potassium methylhydrazine dithiocarbamate with hydrochloric acid, heat under reflux, cool, filter, collect the solid, wash, recrystallize, and obtain MMTD.
[0021] Furthermore, in S1, the mass ratio of ethanol, methylhydrazine, potassium hydroxide, and carbon disulfide is 10:1:(2~2.4):(1.1~1.5).
[0022] Furthermore, in S1, the dropping rate of carbon disulfide is 0.3 g / min to 0.7 g / min.
[0023] In S1, the process conditions for the stirred reaction are: reaction temperature: 0℃~5℃, reaction time: 0.5h~1h.
[0024] Furthermore, in S2, the mass ratio of the reaction solution containing potassium methylhydrazine dithiocarbamate to hydrochloric acid is 1:(2~4).
[0025] Furthermore, in S2, the process conditions for the heating reflux reaction are: heating temperature 85℃~95℃, reaction time 0.5h~1h.
[0026] Furthermore, in S2, the hydrochloric acid is added in solution form with a concentration of 30% to 38%.
[0027] Furthermore, the SPS is prepared by the following process: Step (1): Add acrylic acid dropwise to concentrated sulfuric acid, heat to react until the solution is clear and transparent, reflux to react, cool, precipitate white solid in ice water bath, adjust pH to 5-6, filter, collect precipitate, distill under reduced pressure to obtain 1,3-propanesulfonyl lactone; Step (2): Mix 1,3-propanesulfonyl lactone, water and sodium sulfide, heat to react, cool, filter, concentrate and recrystallize to obtain SPS.
[0028] Furthermore, in step (1), the molar ratio of concentrated sulfuric acid to acrylic acid is (3~5):1; In step (1), the concentration of concentrated sulfuric acid is 98%.
[0029] Furthermore, in step (1), the dropping rate of acrylic acid is 0.1 g / min to 0.3 g / min.
[0030] Furthermore, in step (1), the process conditions for the heating reaction are: reaction temperature 60℃~80℃, reaction time 2h~4h.
[0031] Furthermore, in step (1), the process conditions for the reflux reaction are: reaction temperature 120℃~140℃, reaction time 4h~6h.
[0032] Furthermore, in step (2), the mass ratio of 1,3-propanesulfonyl lactone, water, and sodium sulfide is 1:(3~5):(1.5~2.2).
[0033] Furthermore, in step (2), the process conditions for the heating reaction are: reaction temperature 40℃~50℃, reaction time 5min~10min.
[0034] In the above technical solution, polyethylene glycol has a long-chain structure and acts as an inhibitor. During electroplating, it can preferentially adsorb onto the active sites on the electrode surface, especially in high-current-density areas where copper ions can deposit rapidly, such as the protruding parts of the sputtered copper layer surface. This adsorption forms a relatively stable protective film, hindering the diffusion and deposition of copper ions onto the electrode surface. Because the inhibitory effect is stronger in high-current-density areas, the deposition rate of copper ions in these areas is slowed down, while in low-current-density areas (such as recessed areas), the deposition of copper ions is relatively unaffected or minimally affected. This results in more uniform deposition of copper ions across the entire copper foil surface, preventing localized rapid copper layer growth and the formation of a rough surface, thus contributing to the formation of a dense and smooth coating. By inhibiting the rapid deposition of copper ions, the growth of copper crystals is somewhat restricted, leading to finer copper grains. Fine grains can improve the density and uniformity of the coating, thereby enhancing the overall performance of the composite copper foil, including tensile strength. Because fine grains have more grain boundaries, these boundaries hinder dislocation movement, making it more difficult for the material to undergo plastic deformation under stress, thus improving tensile strength. Using MMTD as a leveling agent, the MMTD molecule contains active groups such as thiol (-SH), which can selectively adsorb onto the microscopic protrusions on the surface of copper foil. During electroplating, the current density at these protrusions is relatively high, and MMTD preferentially adsorbs in these areas, reducing the electrode reactivity at these locations. Due to the adsorption of MMTD, the deposition rate of copper ions at the protrusions is slowed down, while the deposition rate at the depressions is relatively faster. As the electroplating process proceeds, the protrusions are gradually "flattened" and the depressions are gradually filled, making the coating surface smoother. A smooth surface helps reduce stress concentration points, and when the composite copper foil is subjected to tensile force, the stress can be more evenly distributed throughout the material, avoiding premature fracture due to excessive local stress, thereby improving tensile strength. MMTD also participates in the copper electrodeposition process, affecting the growth orientation and structure of copper crystals, making the copper crystals more orderly arranged, further improving the density and smoothness of the coating, and also playing a positive role in improving tensile strength. Using SPS as a brightener, SPS can reduce the overpotential of copper ions being reduced to copper atoms on the electrode surface, promoting the formation of copper crystal nuclei. At the beginning of electroplating, a large number of nuclei form simultaneously, allowing subsequent copper crystals to grow on top of these numerous nuclei, preventing the overgrowth of a single nucleus and the formation of coarse grains. Due to the increased number of nuclei, the growth space for each nucleus is relatively reduced, resulting in fine and uniform copper grains. These fine grains not only give the plating a bright appearance but also significantly improve the density of the plating. The dense plating structure can effectively resist external forces and better disperse stress during stretching, improving the tensile strength of the composite copper foil. SPS also affects the deposition kinetics of copper ions, making the deposition of copper ions on the electrode surface more uniform and stable, contributing to the formation of a smooth and dense plating layer and further enhancing the performance of the composite copper foil.
[0035] Furthermore, before the polypropylene film containing the sputtered copper layer is placed in the electroplating solution, it is first subjected to plasma treatment by introducing a mixed gas.
[0036] Furthermore, the mixed gas consists of oxygen and nitrogen; The flow rate ratio of oxygen to nitrogen is (0.3~0.5):(1~2).
[0037] Furthermore, the plasma treatment process conditions are as follows: mixed gas flow rate 200 sccm~400 sccm, treatment power 300W~500W, and treatment time 1min~3min.
[0038] Furthermore, the electroplating solution also contains modified hydroxyethyl cellulose, and the specific preparation process is as follows: Hydroxyethyl cellulose, p-aminobenzenesulfonic acid, and deionized water were mixed, an initiator was added, and the mixture was heated under a nitrogen atmosphere to obtain modified hydroxyethyl cellulose.
[0039] Furthermore, the mass ratio of hydroxyethyl cellulose, p-aminobenzenesulfonic acid, deionized water and initiator is 1:(0.1~0.5):(5~10):(0.03~0.07).
[0040] Furthermore, the amount of modified hydroxyethyl cellulose added to the electroplating solution is 3~5 g / L.
[0041] Furthermore, the process conditions for the heating reaction are: reaction temperature 45℃~65℃, reaction time 4h~8h.
[0042] Furthermore, the initiator is one or a mixture of potassium sulfate, ammonium persulfate, and azobisisobutyramidine hydrochloride.
[0043] In the above technical solution, hydroxyethyl cellulose can delay the sedimentation of solutes in the electroplating solution, stabilize the composition of the plating solution, increase the viscosity of the plating solution, reduce the surface tension of the plating solution, and reduce the unevenness of the plating surface caused by uneven flow of the plating solution during the electroplating process. Introducing amino and sulfonic acid groups into hydroxyethyl cellulose allows the amino groups to form stable complexes with copper ions in the plating solution and hydrogen bonds with the surface-treated polypropylene film containing the sputtered copper layer, thereby enhancing the interlayer bonding between the copper plating layer and the sputtered copper layer. The sulfonic acid groups have strong hydrophilicity, which can improve the wettability of the electroplating solution, allowing the electroplating solution to cover the surface of the sputtered copper layer more evenly, thus improving the smoothness and density of the coating.
[0044] Furthermore, prior to plasma treatment, a modified hyperbranched polyimide coating is applied to the surface of the polypropylene film containing the sputtered copper layer; the specific process is as follows: A modified hyperbranched polyimide solution was coated onto the surface of a polypropylene film containing a sputtered copper layer, and dried at 100℃~200℃ for 2h~4h to form a modified hyperbranched polyimide coating with a thickness of 0.5μm~1.5μm.
[0045] Furthermore, the modified hyperbranched polyimide solution is prepared by the following process: Step A: Mix 3-mercaptopropyltrimethoxysilane and deionized water, adjust the pH to 8.5-9.5, heat the reaction, add nano-silica, react at room temperature under nitrogen atmosphere, centrifuge, wash, and dry to obtain mercapto-modified silica; Step B: Mix the triamine monomer, dianhydride monomer and N,N-dimethylformamide, and stir the mixture under a nitrogen atmosphere to obtain a hyperbranched polyamic acid solution. Step C: Mix hyperbranched polyamic acid solution, mercaptoized silica and N,N-dimethylformamide, heat to react, add acetic anhydride and pyridine, cool to 45℃~65℃ and react for 4h~6h to obtain modified hyperbranched polyimide solution.
[0046] Furthermore, in step A, the mass ratio of 3-mercaptopropyltrimethoxysilane, deionized water, and nano-silica is 1:(10~20):(1~5).
[0047] Furthermore, in step A, the process conditions for the heating reaction are: heating temperature 60℃~80℃, reaction time 2h~4h; In step A, the process conditions for the room temperature reaction are: temperature 25℃~35℃, reaction time 6h~8h.
[0048] Furthermore, in step B, the mass ratio of the triamine monomer, the dianhydride monomer, and N,N-dimethylformamide is (1~1.5):1:5.
[0049] Furthermore, in step B, the process conditions for the stirring reaction are: reaction temperature 40℃~50℃, reaction time 4h~6h, and stirring speed 150rpm~250rpm.
[0050] Furthermore, in step B, the triamine monomer is one or a mixture of two of tris(4-aminophenyl)amine and 1,3,5-tris(aminophenyl)benzene; The dianhydride monomer is one or a mixture of two of pyromellitic dianhydride and 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride.
[0051] Furthermore, in step C, the mass ratio of hyperbranched polyamic acid solution, mercaptoized silica, N,N-dimethylformamide, acetic anhydride and pyridine is 10:(0.05~0.15):(15~25):(0.1~0.3):(0.01~0.05).
[0052] Furthermore, in step C, the process conditions for the heating reaction are: reaction temperature 80℃~100℃, reaction time 6h~10h.
[0053] In the above technical solution, an amino-terminated hyperbranched polyimide is prepared by triamine monomer, dianhydride monomer and pyridine, and coated on the surface of sputtered copper layer. Its highly branched network structure can improve the tensile strength of composite copper foil by dispersing stress; and the branched structure increases the expandable space of molecular chains when heated, reduces the thermal shrinkage rate, reduces the large thermal deformation of composite current collector during battery cycle, and improves the battery life. The thiol groups in thiolized silica can undergo a ring-opening reaction with the anhydrides in hyperbranched polyamic acid to form amide bonds, which anchor the anhydrides within the hyperbranched polyimide network structure, reducing the agglomeration problem caused by blending and, to a certain extent, improving the tensile strength of the hyperbranched polyimide coating. Furthermore, the dielectric constant of mercapto-modified silica is higher than that of hyperbranched polyimide. Introducing mercapto-modified silica can improve the dielectric constant of the coating and reduce dielectric loss, thereby extending the cycle life and energy density of the battery to a certain extent.
[0054] Compared with the prior art, the beneficial effects of the present invention are: 1. In the electroplating solution of the present invention, polyethylene glycol is used as an inhibitor, MMTD as a leveling agent, and SPS as a brightener. Through the synergistic effect of the three, a composite copper foil with a dense and smooth coating surface and higher tensile strength is obtained, thereby improving the stability of the composite current collector and improving the battery's service life and safety performance.
[0055] 2. The electroplating solution of the present invention also contains modified hydroxyethyl cellulose, which can delay the sedimentation of solutes in the electroplating solution, stabilize the composition of the plating solution, increase the viscosity of the plating solution, reduce the surface tension of the plating solution, and reduce the unevenness of the coating surface caused by uneven flow of the plating solution during the electroplating process. The introduced amino groups can form stable complexes with copper ions in the plating solution on the one hand, and form hydrogen bonds with the surface-treated polypropylene film containing the sputtered copper layer on the other hand, which enhances the interlayer bonding force between the copper plating layer and the sputtered copper layer. The introduced sulfonic acid groups have strong hydrophilicity, which can improve the wettability of the electroplating solution, so that the electroplating solution covers the surface of the sputtered copper layer more evenly, and improve the smoothness and density of the coating.
[0056] 3. The present invention coats the surface of the sputtered copper layer with a modified hyperbranched polyimide solution containing mercapto-modified silica before electroplating. The dielectric constant of mercapto-modified silica is higher than that of hyperbranched polyimide. The introduction of mercapto-modified silica can improve the dielectric constant of the coating and reduce dielectric loss, thereby extending the cycle life and energy density of the battery to a certain extent. The highly branched network structure of modified hyperbranched polyimide can improve the tensile strength of composite copper foil by dispersing stress; and the branched structure increases the expandable space of molecular chains when heated, reduces the thermal shrinkage rate, reduces the large thermal deformation of composite current collector during battery cycling, and improves battery life. Detailed Implementation
[0057] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0058] In the following specific implementation, Ethylene oxide, purity 99.9%; The starting agent is ethylene glycol, with a purity of 99.9%; The catalyst is potassium hydroxide; The neutralizing agent is phosphoric acid; Hydrochloric acid solution, concentration 30%~38%; The initiator is ammonium persulfate; Polypropylene film, 4μm; Copper target material, 99.9% purity; Nano-sized silica, 90nm in diameter; The triamine monomer is tris(4-aminophenyl)amine; The dianhydride monomer is pyromellitic dianhydride; Concentrated sulfuric acid, 98% concentration; The brightener is Jeremy brightener, model 310A; The leveling agent is Jeremy leveling agent, model 200B.
[0059] Example 1: A method for preparing a composite copper foil coating with high surface density and smoothness, comprising the following steps: (1) Preparation of polyethylene glycol: Ethylene oxide, ethylene glycol, and potassium hydroxide were mixed in a mass ratio of 230:1:0.012 and heated under a nitrogen atmosphere. Phosphoric acid was added to adjust the pH to 7.0. The mixture was then filtered, distilled under reduced pressure, and purified to obtain polyethylene glycol with an average molecular weight of 10,000. The process conditions for the heating reaction were: reaction temperature 180℃, reaction time 12h, reaction pressure 0.8MPa, and ethylene oxide feed rate 15kg / h. (2) Preparation of MMTD: S1: Ethanol, methylhydrazine, and potassium hydroxide were mixed, and carbon disulfide was added dropwise at 0.7 g / min at 5 °C. The mixture was stirred to obtain a reaction solution containing potassium methylhydrazine dithiocarbamate. S2: The reaction solution containing potassium methylhydrazine dithiocarbamate was mixed with a 38% hydrochloric acid solution at a mass ratio of 1:4. The mixture was heated under reflux, cooled, filtered, and the solid was collected, washed, and recrystallized to obtain MMTD. The mass ratio of ethanol, methylhydrazine, potassium hydroxide, and carbon disulfide was 10:1:2.4:1.5. In S1, the stirring reaction conditions were: reaction temperature: 5 °C, reaction time: 1 h. In S2, the reflux reaction conditions were: heating temperature: 95 °C, reaction time: 1 h. (3) Preparation of SPS: Step 1: Acrylic acid is added dropwise to concentrated sulfuric acid at a rate of 0.3 g / min. The mixture is heated to 80°C and reacted for 4 h until the solution is clear and transparent. The temperature is then raised to 140°C and refluxed for 6 h. After cooling, a white solid precipitates in an ice-water bath. The pH is adjusted to 6, the mixture is filtered, the precipitate is collected, and distilled under reduced pressure to obtain 1,3-propanesulfonyl lactone. Step 2: 1,3-propanesulfonyl lactone, water, and sodium sulfide are mixed at a mass ratio of 1:5:2.2. The mixture is heated to 50°C and reacted for 10 min. After cooling, the mixture is filtered, concentrated, and recrystallized to obtain SPS. In Step 1, the molar ratio of concentrated sulfuric acid to acrylic acid is 5:1. (4) Preparation of composite copper foil coating: A copper sulfate solution with a concentration of 130 g / L, a hydrochloric acid solution with a concentration of 140 g / L, a brightener, a leveling agent, polyethylene glycol, MMTD, SPS, and deionized water were mixed and stirred until homogeneous to obtain an electroplating solution. The electroplating solution contained 100 g / L of copper sulfate solution, 60 ppm / L of hydrochloric acid solution, 2.5 g / L of brightener and leveling agent, and 1.0 mg / L of polyethylene glycol, MMTD, and SPS. Step 1: Take a polypropylene film and magnetron sputter a copper target onto its surface to form a 60nm thick sputtered copper layer, thus obtaining a polypropylene film containing the sputtered copper layer; Step 2: Place the polypropylene film containing the sputtered copper layer in an electroplating solution and electroplate to form a 1μm thick composite copper foil coating with high surface density and smoothness; The electroplating process conditions are: temperature 35℃, current density 15mA / cm². 2 Electroplating time: 15 minutes.
[0060] Example 2: A method for preparing a composite copper foil coating with high surface density and smoothness, comprising the following steps: (1) Preparation of polyethylene glycol: Ethylene oxide, ethylene glycol, and potassium hydroxide were mixed in a mass ratio of 215:1:0.010 and heated under a nitrogen atmosphere. Phosphoric acid was added to adjust the pH to 6.7. The mixture was then filtered, distilled under reduced pressure, and purified to obtain polyethylene glycol with an average molecular weight of 10,000. The process conditions for the heating reaction were: reaction temperature 150℃, reaction time 10h, reaction pressure 0.5MPa, and ethylene oxide feed rate 10kg / h. (2) Preparation of MMTD: S1: Ethanol, methylhydrazine, and potassium hydroxide were mixed, and carbon disulfide was added dropwise at 0.5 g / min at 3°C with stirring to obtain a reaction solution containing potassium methylhydrazine dithiocarbamate. S2: The reaction solution containing potassium methylhydrazine dithiocarbamate was mixed with a 35% hydrochloric acid solution at a mass ratio of 1:3, heated to reflux, cooled, filtered, and the solid was collected, washed, and recrystallized to obtain MMTD. The mass ratio of ethanol, methylhydrazine, potassium hydroxide, and carbon disulfide was 10:1:2.2:1.3. In S1, the stirring reaction conditions were: reaction temperature: 3°C, reaction time: 0.7 h. In S2, the reflux reaction conditions were: heating temperature: 90°C, reaction time: 0.7 h. (3) Preparation of SPS: Step 1: Acrylic acid is added dropwise to concentrated sulfuric acid at a rate of 0.2 g / min. The mixture is heated to 70°C and reacted for 3 h until the solution is clear and transparent. The temperature is then raised to 130°C and refluxed for 5 h. After cooling, a white solid precipitates in an ice-water bath. The pH is adjusted to 5.5, the mixture is filtered, the precipitate is collected, and the solution is distilled under reduced pressure to obtain 1,3-propanesulfonyl lactone. Step 2: 1,3-propanesulfonyl lactone, water, and sodium sulfide are mixed in a mass ratio of 1:4:1.8. The mixture is heated to 45°C and reacted for 7 min. After cooling, the mixture is filtered, concentrated, and recrystallized to obtain SPS. In Step 1, the molar ratio of concentrated sulfuric acid to acrylic acid is 4:1. (4) Preparation of composite copper foil coating: A copper sulfate solution with a concentration of 100 g / L, a hydrochloric acid solution with a concentration of 120 g / L, a brightener, a leveling agent, polyethylene glycol, MMTD, SPS, and deionized water were mixed and stirred until homogeneous to obtain an electroplating solution. The electroplating solution contained 95 g / L of copper sulfate solution, 58 ppm / L of hydrochloric acid solution, 2.2 g / L of brightener and leveling agent, and 0.8 mg / L of polyethylene glycol, MMTD, and SPS. Step 1: Take a polypropylene film and magnetron sputter a copper target onto its surface to form a 50nm thick sputtered copper layer, thus obtaining a polypropylene film containing the sputtered copper layer; Step 2: Place the polypropylene film containing the sputtered copper layer in an electroplating solution and electroplat it to form a 0.8μm thick composite copper foil coating with high surface density and smoothness; The electroplating process conditions are: temperature 30℃, current density 10mA / cm². 2 Electroplating time: 10 minutes.
[0061] Example 3: A method for preparing a composite copper foil coating with high surface density and smoothness, comprising the following steps: (1) Preparation of polyethylene glycol: Ethylene oxide, ethylene glycol, and potassium hydroxide were mixed in a mass ratio of 200:1:0.006 and heated under a nitrogen atmosphere. Phosphoric acid was added to adjust the pH to 6.5. The mixture was then filtered, distilled under reduced pressure, and purified to obtain polyethylene glycol with an average molecular weight of 10,000. The process conditions for the heating reaction were: reaction temperature 120℃, reaction time 8h, reaction pressure 0.3MPa, and ethylene oxide feed rate 5kg / h. (2) Preparation of MMTD: S1: Ethanol, methylhydrazine, and potassium hydroxide were mixed, and carbon disulfide was added dropwise at 0.3 g / min at 0 °C with stirring to obtain a reaction solution containing potassium methylhydrazine dithiocarbamate. S2: The reaction solution containing potassium methylhydrazine dithiocarbamate was mixed with a 30% hydrochloric acid solution at a mass ratio of 1:2, heated to reflux, cooled, filtered, and the solid was collected, washed, and recrystallized to obtain MMTD. The mass ratio of ethanol, methylhydrazine, potassium hydroxide, and carbon disulfide was 10:1:2:1.1. In S1, the stirring reaction conditions were: reaction temperature: 0 °C, reaction time: 0.5 h. In S2, the reflux reaction conditions were: heating temperature: 85 °C, reaction time: 0.5 h. (3) Preparation of SPS: Step 1: Acrylic acid is added dropwise to concentrated sulfuric acid at a rate of 0.1 g / min. The mixture is heated to 60°C and reacted for 2 h until the solution is clear and transparent. The temperature is then raised to 120°C and refluxed for 4 h. After cooling, a white solid precipitates in an ice-water bath. The pH is adjusted to 5, the mixture is filtered, the precipitate is collected, and distilled under reduced pressure to obtain 1,3-propanesulfonyl lactone. Step 2: 1,3-propanesulfonyl lactone, water, and sodium sulfide are mixed in a mass ratio of 1:3:1.5. The mixture is heated to 40°C and reacted for 5 min. After cooling, the mixture is filtered, concentrated, and recrystallized to obtain SPS. In Step 1, the molar ratio of concentrated sulfuric acid to acrylic acid is 3:1. (4) Preparation of composite copper foil coating: A 70 g / L copper sulfate solution, a 100 g / L hydrochloric acid solution, a brightener, a leveling agent, polyethylene glycol, MMTD, SPS, and deionized water were mixed and stirred until homogeneous to obtain an electroplating solution. The electroplating solution contained 90 g / L of copper sulfate solution, 55 ppm / L of hydrochloric acid solution, 2.0 g / L of brightener and leveling agent, and 0.5 mg / L of polyethylene glycol, MMTD, and SPS. Step 1: Take a polypropylene film and magnetron sputter a copper target onto its surface to form a 40nm thick sputtered copper layer, thus obtaining a polypropylene film containing the sputtered copper layer; Step 2: Place the polypropylene film containing the sputtered copper layer in an electroplating solution and electroplate to form a 0.5μm thick composite copper foil coating with high surface density and smoothness; The electroplating process conditions are: temperature 25℃, current density 5mA / cm². 2 Electroplating time: 5 minutes.
[0062] Example 4: A method for preparing a composite copper foil coating with high surface density and smoothness, comprising the following steps: (1) Preparation of polyethylene glycol: Ethylene oxide, ethylene glycol, and potassium hydroxide were mixed in a mass ratio of 230:1:0.012 and heated under a nitrogen atmosphere. Phosphoric acid was added to adjust the pH to 7.0. The mixture was then filtered, distilled under reduced pressure, and purified to obtain polyethylene glycol with an average molecular weight of 10,000. The process conditions for the heating reaction were: reaction temperature 180℃, reaction time 12h, reaction pressure 0.8MPa, and ethylene oxide feed rate 15kg / h. (2) Preparation of MMTD: S1: Ethanol, methylhydrazine, and potassium hydroxide were mixed, and carbon disulfide was added dropwise at 0.7 g / min at 5 °C. The mixture was stirred to obtain a reaction solution containing potassium methylhydrazine dithiocarbamate. S2: The reaction solution containing potassium methylhydrazine dithiocarbamate was mixed with a 38% hydrochloric acid solution at a mass ratio of 1:4. The mixture was heated under reflux, cooled, filtered, and the solid was collected, washed, and recrystallized to obtain MMTD. The mass ratio of ethanol, methylhydrazine, potassium hydroxide, and carbon disulfide was 10:1:2.4:1.5. In S1, the stirring reaction conditions were: reaction temperature: 5 °C, reaction time: 1 h. In S2, the reflux reaction conditions were: heating temperature: 95 °C, reaction time: 1 h. (3) Preparation of SPS: Step 1: Acrylic acid is added dropwise to concentrated sulfuric acid at a rate of 0.3 g / min. The mixture is heated to 80°C and reacted for 4 h until the solution is clear and transparent. The temperature is then raised to 140°C and refluxed for 6 h. After cooling, a white solid precipitates in an ice-water bath. The pH is adjusted to 6, the mixture is filtered, the precipitate is collected, and distilled under reduced pressure to obtain 1,3-propanesulfonyl lactone. Step 2: 1,3-propanesulfonyl lactone, water, and sodium sulfide are mixed at a mass ratio of 1:5:2.2. The mixture is heated to 50°C and reacted for 10 min. After cooling, the mixture is filtered, concentrated, and recrystallized to obtain SPS. In Step 1, the molar ratio of concentrated sulfuric acid to acrylic acid is 5:1. (4) Preparation of modified hydroxyethyl cellulose: Hydroxyethyl cellulose, p-aminobenzenesulfonic acid, and deionized water were mixed, and ammonium persulfate was added. The mixture was heated to 65°C and reacted for 8 hours under a nitrogen atmosphere to obtain modified hydroxyethyl cellulose. The mass ratio of hydroxyethyl cellulose, p-aminobenzenesulfonic acid, deionized water, and ammonium persulfate was 1:0.5:10:0.07. (5) Preparation of modified hyperbranched polyimide solution: Step A: Mix 3-mercaptopropyltrimethoxysilane and deionized water, adjust the pH to 9.5, heat to 80℃ and react for 4 hours, add nano-silica, and react at 35℃ for 8 hours under nitrogen atmosphere. Centrifuge, wash, and dry to obtain mercapto-modified silica; Step B: Mix tris(4-aminophenyl)amine, pyromellitic dianhydride, and N,N-dimethylformamide in a mass ratio of 1.5:1:5, and stir under nitrogen atmosphere to obtain a hyperbranched polyamic acid solution; Step C: Combine the hyperbranched polyamic acid solution, mercapto-modified silica, and N,N-dimethylformamide. The mixture was heated to 100℃ and reacted for 10 hours. Acetic anhydride and pyridine were added, and the mixture was cooled to 65℃ and reacted for 6 hours to obtain a modified hyperbranched polyimide solution. In step A, the mass ratio of 3-mercaptopropyltrimethoxysilane, deionized water, and nano-silica was 1:20:5. In step B, the reaction conditions were: reaction temperature 50℃, reaction time 6 hours, and stirring speed 250 rpm. In step C, the mass ratio of hyperbranched polyamic acid solution, mercaptoized silica, N,N-dimethylformamide, acetic anhydride, and pyridine was 10:0.15:25:0.3:0.05. (6) Preparation of composite copper foil coating: A copper sulfate solution with a concentration of 130 g / L, a hydrochloric acid solution with a concentration of 140 g / L, a brightener, a leveling agent, polyethylene glycol, MMTD, SPS, deionized water, and modified hydroxyethyl cellulose were mixed and stirred evenly to obtain an electroplating solution. The electroplating solution contained 100 g / L of copper sulfate solution, 60 ppm / L of hydrochloric acid solution, 2.5 g / L of brightener and leveling agent, 1.0 mg / L of polyethylene glycol, MMTD, and SPS, and 5 g / L of modified hydroxyethyl cellulose. Step 1: Take a polypropylene film and magnetron sputter a copper target onto its surface to form a 60nm thick sputtered copper layer, obtaining a polypropylene film containing a sputtered copper layer; Step 2: Coat the surface of the polypropylene film containing the sputtered copper layer with a modified hyperbranched polyimide solution and dry it at 200℃ for 4 hours to form a 1.5μm thick modified hyperbranched polyimide coating; Step 3: Introduce a mixed gas to the modified hyperbranched polyimide coating for plasma treatment; The plasma treatment process conditions are: mixed gas flow rate 400sccm, treatment power 500W, treatment time 3min; The mixed gas is oxygen and nitrogen mixed at a flow rate ratio of 0.5:2; Step 4: Place the plasma-treated composite copper foil in an electroplating solution and electroplat it to form a 1μm thick composite copper foil coating with high surface density and smoothness; The electroplating process conditions are: temperature 35℃, current density 15mA / cm². 2 Electroplating time: 15 minutes.
[0063] Example 5: A method for preparing a composite copper foil coating with high surface density and smoothness, comprising the following steps: (1) Preparation of polyethylene glycol: Ethylene oxide, ethylene glycol, and potassium hydroxide were mixed in a mass ratio of 230:1:0.012 and heated under a nitrogen atmosphere. Phosphoric acid was added to adjust the pH to 7.0. The mixture was then filtered, distilled under reduced pressure, and purified to obtain polyethylene glycol with an average molecular weight of 10,000. The process conditions for the heating reaction were: reaction temperature 180℃, reaction time 12h, reaction pressure 0.8MPa, and ethylene oxide feed rate 15kg / h. (2) Preparation of MMTD: S1: Ethanol, methylhydrazine, and potassium hydroxide were mixed, and carbon disulfide was added dropwise at 0.7 g / min at 5 °C. The mixture was stirred to obtain a reaction solution containing potassium methylhydrazine dithiocarbamate. S2: The reaction solution containing potassium methylhydrazine dithiocarbamate was mixed with a 38% hydrochloric acid solution at a mass ratio of 1:4. The mixture was heated under reflux, cooled, filtered, and the solid was collected, washed, and recrystallized to obtain MMTD. The mass ratio of ethanol, methylhydrazine, potassium hydroxide, and carbon disulfide was 10:1:2.4:1.5. In S1, the stirring reaction conditions were: reaction temperature: 5 °C, reaction time: 1 h. In S2, the reflux reaction conditions were: heating temperature: 95 °C, reaction time: 1 h. (3) Preparation of SPS: Step 1: Acrylic acid is added dropwise to concentrated sulfuric acid at a rate of 0.3 g / min. The mixture is heated to 80°C and reacted for 4 h until the solution is clear and transparent. The temperature is then raised to 140°C and refluxed for 6 h. After cooling, a white solid precipitates in an ice-water bath. The pH is adjusted to 6, the mixture is filtered, the precipitate is collected, and distilled under reduced pressure to obtain 1,3-propanesulfonyl lactone. Step 2: 1,3-propanesulfonyl lactone, water, and sodium sulfide are mixed at a mass ratio of 1:5:2.2. The mixture is heated to 50°C and reacted for 10 min. After cooling, the mixture is filtered, concentrated, and recrystallized to obtain SPS. In Step 1, the molar ratio of concentrated sulfuric acid to acrylic acid is 5:1. (4) Preparation of modified hydroxyethyl cellulose: Hydroxyethyl cellulose, p-aminobenzenesulfonic acid, and deionized water were mixed, and ammonium persulfate was added. The mixture was heated to 55°C and reacted for 6 hours under a nitrogen atmosphere to obtain modified hydroxyethyl cellulose. The mass ratio of hydroxyethyl cellulose, p-aminobenzenesulfonic acid, deionized water, and ammonium persulfate was 1:0.3:7:0.05. (5) Preparation of modified hyperbranched polyimide solution: Step A: Mix 3-mercaptopropyltrimethoxysilane and deionized water, adjust the pH to 9.0, heat to 70℃ and react for 3 hours, add nano-silica, and react at 30℃ for 7 hours under nitrogen atmosphere. Centrifuge, wash, and dry to obtain mercapto-modified silica; Step B: Mix tris(4-aminophenyl)amine, pyromellitic dianhydride, and N,N-dimethylformamide in a mass ratio of 1.3:1:5, and stir under nitrogen atmosphere to obtain a hyperbranched polyamic acid solution; Step C: Combine the hyperbranched polyamic acid solution, mercapto-modified silica, and N,N-dimethylformamide... Amines were mixed and heated to 90°C for 8 hours. Acetic anhydride and pyridine were added, and the mixture was cooled to 55°C and reacted for 5 hours to obtain a modified hyperbranched polyimide solution. In step A, the mass ratio of 3-mercaptopropyltrimethoxysilane, deionized water, and nano-silica was 1:15:3. In step B, the reaction conditions were: reaction temperature 45°C, reaction time 5 hours, and stirring speed 200 rpm. In step C, the mass ratio of hyperbranched polyamic acid solution, mercaptoized silica, N,N-dimethylformamide, acetic anhydride, and pyridine was 10:0.10:20:0.2:0.03. (6) Preparation of composite copper foil coating: A copper sulfate solution with a concentration of 130 g / L, a hydrochloric acid solution with a concentration of 140 g / L, a brightener, a leveling agent, polyethylene glycol, MMTD, SPS, deionized water, and modified hydroxyethyl cellulose were mixed and stirred until homogeneous to obtain an electroplating solution. The electroplating solution contained 100 g / L of copper sulfate solution, 60 ppm / L of hydrochloric acid solution, 2.5 g / L of brightener and leveling agent, 1.0 mg / L of polyethylene glycol, MMTD, and SPS, and 4 g / L of modified hydroxyethyl cellulose. Step 1: Take a polypropylene film and magnetron sputter a copper target onto its surface to form a 60nm thick sputtered copper layer, obtaining a polypropylene film containing a sputtered copper layer; Step 2: Coat the surface of the polypropylene film containing the sputtered copper layer with a modified hyperbranched polyimide solution and dry it at 150℃ for 3 hours to form a 1.0μm thick modified hyperbranched polyimide coating; Step 3: Introduce a mixed gas to the modified hyperbranched polyimide coating for plasma treatment; The plasma treatment process conditions are: mixed gas flow rate 300sccm, treatment power 400W, treatment time 2min; The mixed gas is oxygen and nitrogen mixed at a flow rate ratio of 0.4:1.5; Step 4: Place the plasma-treated composite copper foil in an electroplating solution and electroplat it to form a 1μm thick composite copper foil coating with high surface density and smoothness; The electroplating process conditions are: temperature 35℃, current density 15mA / cm². 2 Electroplating time: 15 minutes.
[0064] Example 6: A method for preparing a composite copper foil coating with high surface density and smoothness, comprising the following steps: (1) Preparation of polyethylene glycol: Ethylene oxide, ethylene glycol, and potassium hydroxide were mixed in a mass ratio of 230:1:0.012 and heated under a nitrogen atmosphere. Phosphoric acid was added to adjust the pH to 7.0. The mixture was then filtered, distilled under reduced pressure, and purified to obtain polyethylene glycol with an average molecular weight of 10,000. The process conditions for the heating reaction were: reaction temperature 180℃, reaction time 12h, reaction pressure 0.8MPa, and ethylene oxide feed rate 15kg / h. (2) Preparation of MMTD: S1: Ethanol, methylhydrazine, and potassium hydroxide were mixed, and carbon disulfide was added dropwise at 0.7 g / min at 5 °C. The mixture was stirred to obtain a reaction solution containing potassium methylhydrazine dithiocarbamate. S2: The reaction solution containing potassium methylhydrazine dithiocarbamate was mixed with a 38% hydrochloric acid solution at a mass ratio of 1:4. The mixture was heated under reflux, cooled, filtered, and the solid was collected, washed, and recrystallized to obtain MMTD. The mass ratio of ethanol, methylhydrazine, potassium hydroxide, and carbon disulfide was 10:1:2.4:1.5. In S1, the stirring reaction conditions were: reaction temperature: 5 °C, reaction time: 1 h. In S2, the reflux reaction conditions were: heating temperature: 95 °C, reaction time: 1 h. (3) Preparation of SPS: Step 1: Acrylic acid is added dropwise to concentrated sulfuric acid at a rate of 0.3 g / min. The mixture is heated to 80°C and reacted for 4 h until the solution is clear and transparent. The temperature is then raised to 140°C and refluxed for 6 h. After cooling, a white solid precipitates in an ice-water bath. The pH is adjusted to 6, the mixture is filtered, the precipitate is collected, and distilled under reduced pressure to obtain 1,3-propanesulfonyl lactone. Step 2: 1,3-propanesulfonyl lactone, water, and sodium sulfide are mixed at a mass ratio of 1:5:2.2. The mixture is heated to 50°C and reacted for 10 min. After cooling, the mixture is filtered, concentrated, and recrystallized to obtain SPS. In Step 1, the molar ratio of concentrated sulfuric acid to acrylic acid is 5:1. (4) Preparation of modified hydroxyethyl cellulose: Hydroxyethyl cellulose, p-aminobenzenesulfonic acid, and deionized water were mixed, and ammonium persulfate was added. The mixture was heated to 45°C and reacted for 4 hours under a nitrogen atmosphere to obtain modified hydroxyethyl cellulose. The mass ratio of hydroxyethyl cellulose, p-aminobenzenesulfonic acid, deionized water, and ammonium persulfate was 1:0.5:10:0.07. (5) Preparation of modified hyperbranched polyimide solution: Step A: Mix 3-mercaptopropyltrimethoxysilane and deionized water, adjust the pH to 8.5, heat to 60℃ and react for 2 hours, add nano-silica, and react at 25℃ for 6 hours under nitrogen atmosphere. Centrifuge, wash, and dry to obtain mercapto-modified silica; Step B: Mix tris(4-aminophenyl)amine, pyromellitic dianhydride, and N,N-dimethylformamide in a mass ratio of 1:1:5, and stir under nitrogen atmosphere to obtain a hyperbranched polyamic acid solution; Step C: Combine the hyperbranched polyamic acid solution, mercapto-modified silica, and N,N-dimethylformamide. The mixture was heated to 80℃ and reacted for 6 hours. Acetic anhydride and pyridine were added, and the mixture was cooled to 45℃ and reacted for 4 hours to obtain a modified hyperbranched polyimide solution. In step A, the mass ratio of 3-mercaptopropyltrimethoxysilane, deionized water, and nano-silica was 1:10:1. In step B, the reaction conditions were: reaction temperature 40℃, reaction time 4 hours, and stirring speed 150 rpm. In step C, the mass ratio of hyperbranched polyamic acid solution, mercaptoized silica, N,N-dimethylformamide, acetic anhydride, and pyridine was 10:0.05:15:0.1:0.01. (6) Preparation of composite copper foil coating: A copper sulfate solution with a concentration of 130 g / L, a hydrochloric acid solution with a concentration of 140 g / L, a brightener, a leveling agent, polyethylene glycol, MMTD, SPS, deionized water, and modified hydroxyethyl cellulose were mixed and stirred evenly to obtain an electroplating solution. The electroplating solution contained 100 g / L of copper sulfate solution, 60 ppm / L of hydrochloric acid solution, 2.5 g / L of brightener and leveling agent, 1.0 mg / L of polyethylene glycol, MMTD, and SPS, and 3 g / L of modified hydroxyethyl cellulose. Step 1: Take a polypropylene film and magnetron sputter a copper target onto its surface to form a 60nm thick sputtered copper layer, obtaining a polypropylene film containing a sputtered copper layer; Step 2: Coat the surface of the polypropylene film containing the sputtered copper layer with a modified hyperbranched polyimide solution and dry it at 100℃ for 2 hours to form a 0.5μm thick modified hyperbranched polyimide coating; Step 3: Introduce a mixed gas to the modified hyperbranched polyimide coating for plasma treatment; The plasma treatment process conditions are: mixed gas flow rate 200sccm, treatment power 300W, treatment time 1min; The mixed gas is oxygen and nitrogen mixed at a flow rate ratio of 0.3:1; Step 4: Place the plasma-treated composite copper foil in an electroplating solution and electroplat it to form a 1μm thick composite copper foil coating with high surface density and smoothness; The electroplating process conditions are: temperature 35℃, current density 15mA / cm². 2 Electroplating time: 15 minutes.
[0065] Comparative Example 1: Compared with Example 1, polyethylene glycol, MMTD and SPS were not added to the electroplating solution, and the other conditions remained the same.
[0066] Comparative Example 2: Compared with Example 1, only polyethylene glycol, MMTD, copper sulfate solution and hydrochloric acid solution were added to the electroplating solution, while the other conditions remained unchanged.
[0067] Comparative Example 3: Compared with Example 1, only polyethylene glycol, SPS, copper sulfate solution and hydrochloric acid solution were added to the electroplating solution, while the other conditions remained unchanged.
[0068] Comparative Example 4: Compared with Example 1, only MMTD, SPS, copper sulfate solution and hydrochloric acid solution were added to the electroplating solution, while the other conditions remained unchanged.
[0069] Comparative Example 5: Compared with Example 1, only polyethylene glycol, copper sulfate solution and hydrochloric acid solution were added to the electroplating solution, while the other conditions remained unchanged.
[0070] Comparative Example 6: Compared with Example 1, only MMTD, copper sulfate solution and hydrochloric acid solution were added to the electroplating solution, while the other conditions remained unchanged.
[0071] Comparative Example 7: Compared with Example 1, only SPS, copper sulfate solution and hydrochloric acid solution were added to the electroplating solution, while the other conditions remained unchanged.
[0072] Comparative Example 8: Compared with Example 4, no modified hydroxyethyl cellulose was added to the electroplating solution, and all other conditions remained the same.
[0073] Comparative Example 9: Compared with Example 4, the modified hyperbranched polyimide solution was not coated, and all other conditions remained the same.
[0074] Experiment: The composite copper foil obtained in the examples and comparative examples was cut into 10*10cm samples and subjected to various performance tests. Tensile strength: The tensile strength of the composite copper foil was tested according to GB / T1040.3-2006; Density test: The composite copper foil sample was analyzed, and the porosity of the coating was obtained by gray scale method to characterize the density of the coating. Roughness test: The surface roughness of the composite copper foil is tested using a roughness tester;
[0075] Based on the data in the table above, the following conclusions can be drawn: Compared with Example 1, in the electroplating solutions of Comparative Examples 1 to 7, without the addition of polyethylene glycol, MMTD and SPS, the tensile strength and density decreased, and the roughness increased, indicating that the polyethylene glycol, MMTD and SPS added in this invention can promote the improvement of the performance of composite copper foil. Compared with Example 1, the electroplating solution of Example 4 was modified with hydroxyethyl cellulose, and a modified hyperbranched polyimide solution was coated on the surface of the sputtered copper layer. The properties of the resulting composite copper foil were improved. This is because the amino groups in the modified hydroxyethyl cellulose can form stable complexes with copper ions in the plating solution and form hydrogen bonds with the surface-treated polypropylene film containing the sputtered copper layer, thereby enhancing the interlayer bonding force between the copper plating layer and the sputtered copper layer. The sulfonic acid groups in the modified hydroxyethyl cellulose have strong hydrophilicity, which can improve the wettability of the electroplating solution, allowing the electroplating solution to cover the surface of the sputtered copper layer more evenly, and improving the smoothness and density of the coating. Compared with Example 4, the electroplating solution of Comparative Example 8 did not contain modified hydroxyethyl cellulose, resulting in a decrease in the density and an increase in the roughness of the composite copper foil. Compared with Example 4, the tensile strength of the composite copper foil obtained in Comparative Example 9 without coating with modified hyperbranched polyimide solution decreased significantly. In summary, it can be seen that the settings of materials and process parameters used in this invention can promote the improvement of tensile strength and density of the resulting composite copper foil, and reduce surface roughness.
[0076] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. A method for preparing a composite copper foil coating with high surface density and smoothness, characterized in that: Includes the following steps: Step 1: Take a polypropylene film and magnetron sputter a copper target onto its surface to form a sputtered copper layer, thus obtaining a polypropylene film containing a sputtered copper layer. Step 2: Place the polypropylene film containing the sputtered copper layer in the electroplating solution and electroplat it to form a composite copper foil coating with high surface density and smoothness. The electroplating solution comprises the following components: copper sulfate, hydrochloric acid, brightener, leveling agent, polyethylene glycol, MMTD, and SPS.
2. The method for preparing a high surface density and smoothness composite copper foil coating according to claim 1, characterized in that: In step 1, the thickness of the polypropylene film is 4 μm.
3. The method for preparing a high surface density and smoothness composite copper foil coating according to claim 1, characterized in that: In step 1, the thickness of the sputtered copper layer is 40nm~60nm.
4. The method for preparing a high surface density and smoothness composite copper foil coating according to claim 3, characterized in that: In step 2, the thickness of the composite copper foil coating is 0.5μm~1μm.
5. The method for preparing a high surface density and smoothness composite copper foil coating according to claim 4, characterized in that: In step 2, the electroplating process conditions are: temperature 25℃~35℃, current density 5mA / cm². 2 ~15mA / cm 2 Electroplating time: 5 min to 15 min.
6. The method for preparing a composite copper foil coating with high surface density and smoothness according to claim 1, characterized in that: The copper sulfate is added in the form of a solution with a concentration of 70 g / L to 130 g / L.
7. The method for preparing a high surface density and smoothness composite copper foil coating according to claim 1, characterized in that: The hydrochloric acid is added in the form of a solution with a concentration of 100 g / L to 140 g / L.
8. The method for preparing a composite copper foil coating with high surface density and smoothness according to claim 1, characterized in that: The polyethylene glycol, MMTD, and SPS were all added in solution form, and the concentrations of polyethylene glycol, MMTD, and SPS were all 0.5 mg / L to 1.0 mg / L.
9. The method for preparing a composite copper foil coating with high surface density and smoothness according to claim 1, characterized in that: The electroplating solution also contains modified hydroxyethyl cellulose, and the preparation process of the modified hydroxyethyl cellulose is as follows: Hydroxyethyl cellulose, p-aminobenzenesulfonic acid, and deionized water were mixed, an initiator was added, and the mixture was heated under a nitrogen atmosphere to obtain modified hydroxyethyl cellulose.
10. The method for preparing a composite copper foil coating with high surface density and smoothness according to claim 1, characterized in that: The surface of the polypropylene film containing the sputtered copper layer is further provided with a modified hyperbranched polyimide coating, which is prepared by the following process: Step A: Mix 3-mercaptopropyltrimethoxysilane and deionized water, adjust the pH to 8.5-9.5, heat the reaction, add nano-silica, react at room temperature under nitrogen atmosphere, centrifuge, wash, and dry to obtain mercapto-modified silica; Step B: Mix the triamine monomer, dianhydride monomer and N,N-dimethylformamide, and stir the mixture under a nitrogen atmosphere to obtain a hyperbranched polyamic acid solution. Step C: Mix hyperbranched polyamic acid solution, mercaptoized silica and N,N-dimethylformamide, heat to react, add acetic anhydride and pyridine, cool to 45℃~65℃ and react for 4h~6h to obtain modified hyperbranched polyimide solution.